A project proposal for an audio-visual orientation tape on broadcasting 121 (course description introduction to audio-visual procedures). - Arellano, Alex
Broadcasting 121 (course description: Introduction to Audio-Visual Procedures) is one of the most grueling courses ever devised for Broadcasting majors. Broadcasting 121 truly separates the man from the boys, the artists from the dilletantes, the TV directors from the mere production assistants.